2017
DOI: 10.1016/j.arth.2017.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Are Instrumented Knee Forces Representative of a Larger Population of Cruciate-Retaining Total Knee Arthroplasties?

Abstract: Background It is not known if the loads and motions reported for instrumented knees are generalizable to a larger population of total knee replacement (TKR) patients. The purpose of this study is to: 1) report axial implant force data for chair and stair activities for a population of cruciate-retaining TKR patients and 2) compare the population forces to those measured with instrumented TKRs. Methods Twenty-three subjects with a cruciate-retaining TKR underwent motion analysis during stair ascending, stair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The tibia was cut 16cm distal to the joint and an intramedullary rod inserted, held in place by a transcortical interference screw. The head of the fibula was screwed to the tibia to maintain the anatomy and function of the lateral collateral ligament [30][31][32]. The quadriceps tendons, iliotibial band (ITB) and hamstrings tendons were individually dissected and bound in fabric, following a previously described method, to enable tendon loading in the rig [33].…”
Section: Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…The tibia was cut 16cm distal to the joint and an intramedullary rod inserted, held in place by a transcortical interference screw. The head of the fibula was screwed to the tibia to maintain the anatomy and function of the lateral collateral ligament [30][31][32]. The quadriceps tendons, iliotibial band (ITB) and hamstrings tendons were individually dissected and bound in fabric, following a previously described method, to enable tendon loading in the rig [33].…”
Section: Specimensmentioning
confidence: 99%
“…This loading was similar to the resting loading across a knee joint (e.g. during sitting) and was applied to ensure the joint surfaces were in contact during the otherwise passive stability measurements, eliminating separation of the articular surfaces [30][31][32]. A Steinmann pin was drilled mediolaterally approximately 50mm distal to the tibial joint line, perpendicular to the shaft, from which two semi-circular hoops were hung, one anterior, the other posterior with a cord attached, each passed over a pulley such that anterior/posterior drawer force could be applied without imposing a rotational torque.…”
Section: Testing Rigmentioning
confidence: 99%
“…ADL loads were based on published instrumented TKR data; however, those studies used posterior‐stabilized TKR, which may limit the applicability to the implants investigated in this study. Previous computational modeling studies have suggested that this load data may be suitable even for CR TKR, but extrapolation to the intact knee may be unreliable. Regardless, the primary focus was on comparing two different TKR bearing designs, and with a lack of alternatives, the proposed standardized loads seem most suitable.…”
Section: Discussionmentioning
confidence: 99%
“…25 The effect of this change was not investigated using the ISO standard, however, and only investigated changes in AP translation. The current direction of the field has shifted toward multi-activity and patient-specific gait data, 29 and while this is an important step, the standard should not be ignored, as it is still relevant for regulatory approval, preclinical testing, and for comparison to other studies. The large differences between the old and new versions of the ISO standard indicate that care should be taken when comparing preclinical tests and wear studies that utilized different versions of the standard.…”
Section: Discussionmentioning
confidence: 99%